The effect of social welfare, emotions and negative perception of the world on fear of crime in Mexico - Rodríguez, Carolina (2024)
In Mexico, insecurity and fear of crime had been affected Mexican’s society historically. However, research has focused on comprehend the causes society attributes to both phenomena increasing and a little has been explored about the relationship those variables can have with concepts like social well-being. This study aims to know about the effect social well-being (and his dimensions), emotions (positive and negative) and negative perception of the world have on the fear of crime. A sample of 152 young students (55.3% women and 44.7% men) with a mean age of 25.56 years (SD= 3.30) participated in this research.Results showed that fear of crime has configurated as a problem itself and affects society in a differential way. Consequently, high levels of social well-being diminish worry about fear of crime. In opposition, high levels of negative perception of the world and of negative feelings, including low levels of social well-being and positive emotions promote higher levels of worry about fear of crime.